Benchmark Discrepancies and Mutual Fund Performance Evaluation. (5th March 2022) - Cremers, K. J. Martijn; Fulkerson, Jon A.; Riley, Timothy B.
Abstract: We introduce a new holdings-based procedure to identify whether a mutual fund has a benchmark discrepancy, which we define as a benchmark other than the prospectus benchmark best matching a fund's investment strategy. We find that funds with a benchmark discrepancy tend to be riskier than their prospectus benchmarks indicate. As a result, the funds on average outperform their prospectus benchmarks, before further risk adjustments, despite underperforming the benchmarks that best match their portfolios.